Sodium Iodide Symporter (NIS)-Mediated Radiovirotherapy for Pancreatic Cancer - Penheiter, Alan R. (2010)
OBJECTIVE: We have previously shown the therapeutic efficacy of an engineered oncolytic measles virus expressing the sodium iodide symporter reporter gene (MV-NIS) in mice with human pancreatic cancer xenografts. The goal of this study was to determine the synergy between MV-NIS-induced oncolysis and NIS-mediated (131)I radiotherapy in this tumor model. MATERIALS AND METHODS: Subcutaneous human BxPC-3 pancreatic tumors were injected twice with MV-NIS. Viral infection, NIS expression, and intratumoral iodide uptake were quantitated with (123)I micro-SPECT/CT. Mice with MV-NIS infected tumors were treated with 0, 37, or 74 MBq (131)I and monitored for tumor progression and survival. Additional studies were performed with stable NIS-expressing tumors (BxPC-3-NIS) treated with 0, 3.7, 18.5, 37, or 74 MBq of (131)I. RESULTS: Mice treated with intratumoral MV-NIS exhibited significant tumor growth delay (p<0.01) and prolonged survival (p=0.02) compared with untreated mice. Synergy between MV-NIS-induced oncolysis and NIS-mediated (131)I ablation was not seen; however, a significant correlation was observed between NIS-mediated intratumoral iodide localization (% ID/g) and peak tumor volume reduction (p=0.04) with combination MV-NIS and (131)I therapy. Stably-transduced NIS-expressing BxPC-3 tumors exhibited rapid regression with ≥18.5 MBq (131)I. CONCLUSION: Delivery of (131)I radiotherapy to NIS-expressing tumors can be optimized using micro-SPECT/CT image guidance. Significant hurdles exist for NIS as a therapeutic gene for combined radiovirotherapy in this human pancreatic cancer model. The lack of synergy observed with MV-NIS and (131)I in this model was not due to a lack of radiosensitivity, but rather to a non-uniform intratumoral distribution of MV-NIS infection.